Histomorphometric study of renal corpuscles of human and goat - Gulam Rasool (Wolters Kluwer Medknow Publications, 2021)
Background: The nephron is the functional and structural unit of the kidney and greatly varies in its structure among different vertebrates; also the formation of nephron shows a variable degree of differences among species. This study was done to compare the size of the renal corpuscle, glomerulus, and urinary space between human and goat kidneys. Methodology: This observational descriptive type of the study was done in the Department of Anatomy, Government Medical College, Kota from December 2019 to January 2021, after seeking proper approval from the Institutional Review Board and Ethical Committee for the study. Seventy human and 70 goat kidney tissues were taken for this study. The stained sections were studied under light microscopy for the diameter of renal corpuscles and glomeruli were measured in ×400 by MICAPS camera and software attached on microscope. The observed data were analyzed, and calculated by MedCalc software version 20.0.3. Data were subjected to independent sample t-test and results were compared and were considered significant at P < 0.05. Results: The renal corpuscles had the mean greatest and least diameter of 131.57 μ and 131.49 μ in humans. While respective values were 157.95 μ and 142.61 μ in goats. The glomeruli had mean maximum and minimum diameter of 112.80 μ and 111.60 μ in humans and 128.20 μ and 119.59 μ in goats. Mean urinary space distance that was 9.66 μ and 13.19 μ in humans and goats, respectively. Conclusions: The present is useful for anatomists and veterinary doctors, comparative anatomists, anthropologists, and histologists.